2007
DOI: 10.1002/prot.21727
|View full text |Cite
|
Sign up to set email alerts
|

Screening of the active site from water by the incoming ligand triggers catalysis and inhibition in serine proteases

Abstract: The pKa of the catalytic His57 N(epsilon)H in the tetrahedral complex (TC) of chymotrypsin with trifluoromethyl ketone inhibitors is 4-5 units higher relative to the free enzyme (FE). Such stable TC's, formed with transition state (TS) analog inhibitors, are topologically similar to the catalytic TS. Thus, analysis of this pKa shift may shed light on the role of water solvation in the general base catalysis by histidine. We applied our QM/SCRF(VS) approach to study this shift. The method enables explicit quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(46 citation statements)
references
References 60 publications
2
44
0
Order By: Relevance
“…As such, our investigations have provided an intriguing and unexpected insight into the function of membrane-immersed proteases; guaranteeing water supply to the catalytic residues at the time of hydrolysis is indeed a deliberate strategy for ensuring catalysis proceeds efficiently. In fact, recent work suggests that catalysis by soluble serine proteases actually requires water desolvation from the active site (Shokhen et al, 2008). Water retention at a specialized site could thus even be more widely applicable to general proteases, especially those that process hydrophobic substrates, although this awaits further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…As such, our investigations have provided an intriguing and unexpected insight into the function of membrane-immersed proteases; guaranteeing water supply to the catalytic residues at the time of hydrolysis is indeed a deliberate strategy for ensuring catalysis proceeds efficiently. In fact, recent work suggests that catalysis by soluble serine proteases actually requires water desolvation from the active site (Shokhen et al, 2008). Water retention at a specialized site could thus even be more widely applicable to general proteases, especially those that process hydrophobic substrates, although this awaits further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the binding of substrates or structurally related inhibitors will induce a conformational change resulting in steric compression between histidine-57 and aspartate-102 and the formation of a low barrier hydrogen bond raising the pK a of histidine-57 [37,38]. Recent calculations [39,40] support the proposal [15,41] that inhibitor or substrate binding causes desolvation of the active site histidine residue in the serine proteases raising the pK a of the histidine residue and allowing it to be an effective general base catalyst enhancing the nucleophilicity of the hydroxyl group of serine-195 [15,21,33,41]. Raising the histidine pKa also allows it to act as a general acid catalyst for the breakdown of the tetrahedral intermediate [13-15, 21, 42] and to stabilize oxyanion formation [15,21].…”
Section: Discussionmentioning
confidence: 99%
“…[22] The heterogeneous combined protein/water environmental effect were accounted for by the QM/SCRF(VS) approach [23] by the continuum solvation COSMO algorithm [24] implemented in MOPAC2009. W1 and W2 were calculated for every CS on a wide interval (from 1 to 80) of dielectric constant of the polarized continuum.…”
Section: Methodsmentioning
confidence: 99%